POPULATION ECOLOGY ITS THEORETICAL FOUNDATIONS - Tulkin Kuiliev (American Journals Publishing, 2024)
The article analyzes the main factors in the formation of the ecological culture of the population, the actions taken to solve this problem, the nature of environmental problems, especially the problems related to the use of natural resources, the problems related to the environment in each country and in the global environment in the multipolar world trend.
Keywords: Ecological culture, ecological problems, natural resources, globalization, multipolar world, trend, environment.